Traceability using RFID and its formulation for a kiwifruit supply chain. (January 2017) - Gautam, Rahul; Singh, Agnisha; Karthik, K.; Pandey, S.; Scrimgeour, F.; Tiwari, M.K.
Highlights: To analyze the impact of traceability of kiwifruit supply chain using Radio Frequency Identification (RFID). To minimize the Transportation cost and RFID implementing cost. To minimize the liability costs on occurrence of contamination. Abstract: Traceability is one of the most important requirements in a fruit supply chain. It helps in keeping a track over the quality, perishability and freshness of the fruits which are the foremost concern for maintaining customer satisfaction. In this paper, we consider a case of kiwifruit supply chain and analyze the impact of traceability using Radio Frequency Identification (RFID) tags. A multi-objective integer non-linear programming model (MOINLP) is formulated considering two objective functions which include (i) minimization of the total costs incorporating logistics costs and costs of implementing RFID tags and (ii) minimization of liability costs on occurrence of contamination. To compute this problem, a newly developed approach of Plant Pollinator Optimization Algorithm (PPO) has been implemented and a comparison with the well-known Non-dominated Sorting Genetic Algorithm-II (NSGA-II) is performed. Insights evolving out of this study can help the Supply Chain Managers in minimizing the risks of delivery of perished fruits by tracing it at an earlier stage and thus reducing the liability costs.